Effective Prolonged Therapy with Voriconazole in a Lung Transplant Recipient with Spondylodiscitis Induced by Scedosporium apiospermum - B. Luijk; M. B. Ekkelenkamp; P. A. De Jong; J. M. Kwakkel-van Erp; J. C. Grutters; D. A. van Kessel; E. A. van de Graaf (Case Reports in Infectious Diseases)
Scedosporium/Pseudallescheria species are frequently seen in cystic fibrosis patients. However, disseminated forms after lung transplantation in these patients are rarely seen, but often with poor outcome. In this case report we describe a lung transplant recipient with cystic fibrosis who developed a spondylodiscitis that was caused by Scedosporium apiospermum. The patient was treated with anti-fungal treatment by voriconazole for over three years with a clinical good response and without the need for surgical intervention. To our opinion this is the first anti-fungal treated case of invasive disease caused by Scedosporium/Pseudallescheria in a cystic fibrosis (CF) patient who underwent lung transplantation that survived.